COGNITIVE FACTORS OF SECOND LANGUAGE LEARNING (Ustozlar uchun, 2025)
This article explores the cognitive factors that influence second language acquisition. Cognitive aspects, such as memory, attention, perception, problem-solving skills, and metacognitive strategies, play a crucial role in learning a new language. The study emphasizes how learners’ cognitive abilities affect their language proficiency, retention, and overall performance. Understanding these factors can help teachers design more effective instructional methods tailored to students’ cognitive strengths and weaknesses.